2019
DOI: 10.1002/ecy.2874
|View full text |Cite
|
Sign up to set email alerts
|

Intraguild predation enables coexistence of competing phytoplankton in a well‐mixed water column

Abstract: Citation: Moeller, H. V., M. G. Neubert, and M. D. Johnson. 2019. Intraguild predation enables coexistence of competing phytoplankton in a well-mixed water column. Ecology 100(12):Abstract. Resource competition theory predicts that when two species compete for a single, finite resource, the better competitor should exclude the other. However, in some cases, weaker competitors can persist through intraguild predation, that is, by eating their stronger competitor. Mixotrophs, species that meet their carbon deman… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 21 publications
(15 citation statements)
references
References 72 publications
(230 reference statements)
0
15
0
Order By: Relevance
“…In particular, light is assumed to attenuate from a surface input irradiance of I in with depth due to absorption by photosynthetic cells which have a per-cell absorptivity k. Huisman and Weissing computed the average photosynthetic rate across depth, and obtained the per capita photosynthetic growth rate, defined here as P( θ , z, I in , T, M ): Mixotrophs also obtain resources by grazing on bacteria. Therefore, we included a grazing term (sensu Moeller et al 2019 [41]) assuming that, at relevant bacterial population densities, mixotroph grazing on bacteria at density B can be approximated using a Type I functional response [42], where α ( θ , T) represents the mixotroph attack rate and b represents the conversion efficiency of captured bacteria into mixotroph biomass: Metabolic rates are known to scale with temperature [3]. To simplify our model, we assume that photosynthetic and grazing rates are linear functions of temperature (Figure 1B): Here, θ is an investment parameter that controls the reliance of mixotrophs on phagotrophy and photosynthesis.…”
Section: Methodsmentioning
confidence: 99%
“…In particular, light is assumed to attenuate from a surface input irradiance of I in with depth due to absorption by photosynthetic cells which have a per-cell absorptivity k. Huisman and Weissing computed the average photosynthetic rate across depth, and obtained the per capita photosynthetic growth rate, defined here as P( θ , z, I in , T, M ): Mixotrophs also obtain resources by grazing on bacteria. Therefore, we included a grazing term (sensu Moeller et al 2019 [41]) assuming that, at relevant bacterial population densities, mixotroph grazing on bacteria at density B can be approximated using a Type I functional response [42], where α ( θ , T) represents the mixotroph attack rate and b represents the conversion efficiency of captured bacteria into mixotroph biomass: Metabolic rates are known to scale with temperature [3]. To simplify our model, we assume that photosynthetic and grazing rates are linear functions of temperature (Figure 1B): Here, θ is an investment parameter that controls the reliance of mixotrophs on phagotrophy and photosynthesis.…”
Section: Methodsmentioning
confidence: 99%
“…However, some constitutive mixotrophs show a stronger reliance on heterotrophy, as is the case for several chrysophytes. Unfortunately, evolutionary relatedness does not align well with differences in physiological strategies of mixotrophs, and closely related strains can show divergent ecophysiologies differing in both resource requirements and responses to environmental conditions (Moeller et al 2019;Wilken et al 2020). This makes inferences of functional roles in nature difficult.…”
Section: Constitutive Mixotrophymentioning
confidence: 99%
“…Phagotrophic algae, one common type of mixotrophs, are capable of acquiring carbon from photosynthesis as well as ingestion of prey ( Stoecker, 1998 ; Mitra et al, 2016 ). Many studies have found that phagotrophic algae can benefit from prey ingestion, which allows them to thrive in the waters where the resource availability (e.g., inorganic nutrients and light) is limited to strict autotrophs ( Wilken et al, 2014 ; Moeller et al, 2019 ). Although there is increasing recognition and understanding of the ecological significance of mixotrophic protists, it remains substantially understudied how phagotrophic algae take advantage of mixotrophic metabolisms in rapidly changing environments.…”
Section: Introductionmentioning
confidence: 99%